2007
DOI: 10.1007/s00530-007-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

An analytical evaluation of search by content and interaction patterns on multimodal meeting records

Abstract: It has been suggested that combining contentbased indexing with automatically generated temporal metadata might help improve search and browsing of recordings of computer-mediated collaborative activities such as on-line meetings, which are characterised by extensive multimodal communication. This paper presents an analytical evaluation of the effectiveness of these techniques as implemented through automatic speech recognition and temporal mapping. In particular, it assesses the extent to which this strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…One might object to our methods arguing that it is wholly un-natural to consider transcripts instead of underlying audio recordings, or better, full-multimodal corpora such as Campbell [5] collected, or more fruitful to ignore text [3]. Researchers have demonstrated that very rich data sources can be tapped to measure interlocutor involvement in conversation, measuring articulation rates, voice intensity, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One might object to our methods arguing that it is wholly un-natural to consider transcripts instead of underlying audio recordings, or better, full-multimodal corpora such as Campbell [5] collected, or more fruitful to ignore text [3]. Researchers have demonstrated that very rich data sources can be tapped to measure interlocutor involvement in conversation, measuring articulation rates, voice intensity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…3 The conversations are relatively balanced in the contributions made by participants, and when watches the accompanying video, one notices a high level of mutual engagement. It is reasonable to take these conversations as representative of engaged, balanced conversation.…”
Section: Case Study 1: English As Lingua Franca In Balanced Chatmentioning
confidence: 99%
“…This may be at the rich level of description afforded by conversational analysis [18] or at more abstract levels [14,2]. For example, the temporal flow of patterns of silence and non-silence are useful in explicating the structure of discussions and their social dynamics [3]. Consider the regular grammar in (1).…”
Section: Dialogue Symbol Sequencesmentioning
confidence: 99%
“…Another interpretation is that v i is the proposition that a total vocalization of some sort is happening. 3 On this interpretation, because the proposition is stative, each proper sub-interval of the duration of v i is also an interval in which the total vocalization is happening, and v i holds true, even if the total vocalization is incomplete over the sub-interval. This property does not hold as cleanly for the first interpretation, as at a proper sub-interval of the duration of v i , v i itself cannot be correctly said to have been vocalized; rather, a proper part of v i is vocalized over the sub-interval.…”
Section: S {Pmentioning
confidence: 99%
“…Metadata tags also for search optimisation have been stored in an extensible markup language (XML) file to contain timestamps of when a participant types a document during a meeting [18,19]. Attempts have been made to automatically identify where decisions are made during a meeting [20].…”
Section: State-of-the-artmentioning
confidence: 99%